A Generalization of Causal Chain Models (Part III of a Triptych on Causal Chain Systems) - Wold, H. O. A. (Econometrica, 1960)
The parting of the ways between causal chain (recursive) and interdependent (nonrecursive) systems is reviewed from the point of view of explanatory relations specified in terms of conditional expectations. On the customary assumptions, a causal chain system is designed so that its relations both in the original form and in the reduced form can be specified in terms of conditional expectations, whereas the relations of interdependent systems allow such specification only in the reduced form. A third type of model is discussed, called conditional causal chains, which formally is similar to interdependent systems, with the important difference that the behavioural relations of the original system are specified in terms of conditional expectations.